Structure of the RNA-dependent RNA polymerase from influenza C virus - Hengrung, N (2014)
The influenza virus causes a disease that kills approximately 500,000 people worldwide each year. Influenza is a negative-sense RNA virus that encodes its own RNA-dependent RNA polymerase. This protein (FluPol) carries out both genome replication and viral transcription. Therefore, like the L-proteins of non-segmented negative-sense RNA (nsRNA) viruses, FluPol also contains mRNA capping and polyadenylation functionality. In FluPol, capping is achieved by snatching cap structures from cellular mRNAs, so requiring cap-binding and endonuclease activities. This makes FluPol a substantial machine. It is a heterotrimeric complex, composed of PB1, PB2 and PA/P3 subunits, with a total molecular weight of 255 kDa. PB1 houses the polymerase active site, whereas PB2 and PA contain, respectively, cap-binding and endonuclease domains. Currently, we only have high resolution structural information for isolated fragments of FluPol. This severely hampers our understanding of influenza replication and consequently inhibits the development of therapies against the virus. In this DPhil project, I have determined a preliminary structure for the heterotrimeric FluPol of influenza C/Johannesburg/1/66, solved by x-ray crystallography to 3.6 Å. Overall, FluPol has an elongated structure with a conspicuous deep groove. PB1 displays the canonical right-hand-like polymerase fold. It sits at the centre of the particle, sandwiched between the two domains of P3, and with PB2 stacked against one side of this dimer. In the structure, the polymerase and endonuclease catalytic sites are both ~40 Å away from the cap-binding pocket. This pocket also faces a tunnel leading to the polymerase core. This suggests a mechanism for how capped cellular mRNAs are cleaved and then fed into the polymerase active site to prime transcription. The structure also hints at a unique trajectory for template RNA, in which the RNA exits at an angle ~180° from which it came in. This provides an explanation for how the polymerases of influenza, and other nsRNA viruses, can copy templates that are packaged into ribonucleoprotein complexes. My work reveals the first molecular structure of any polymerase from an nsRNA virus. It uncovers the arrangement of functional domains within FluPol, illuminating the mechanisms of this and related viral polymerases. This work will help focus future experiments into FluPol biology, and should hopefully spur the development of novel antiviral drugs.